The knowledge and awareness of the importance of respirator fit testing - Cheng Siang, Tan; Ashley Edward Roy, Soosay (2022)
Background: The emergence of the SARS-CoV-2 has caught the world off guard. In the nick of time, respirators and other personal protective equipment turned into highly priced commodities. Many healthcare workers donned respirators for the first time, some donned surgical masks and interchanged them with respirators, depending on their availability. Respirators work by achieving a tight seal with the operators’ face in which respirator fit can be determined via respirator fit testing. Infectious aerosol can be inhaled via the leak, endangering the health of the users. Therefore, the objective of this study is to determine the knowledge and awareness of respirator fit testing among the healthcare workers at the time of the SARS-CoV-2 pandemic in Sarawak, Malaysia. Methods: We conducted an online workshop called “Proper use of facemask & respirator at the time of COVID-19 pandemic” with the objective of providing an authoritative guidance on the selection and use of various face coverings and respirators. The workshop was hosted live via Facebook and YouTube. At the end of it, we provided self-administered questionnaires to gauge the knowledge and awareness of the participants. Results: The workshop was attended by 280 participants, of which 188 responded to the questionnaire. Slightly more than half (52.7%, n=99/188) of the respondents have never heard about respirator fit testing. Most of the participants were healthcare workers (76.6%, n=144/188) and 70.8% (n=102/144) of them mentioned the requirement of respirator use at work. However, only 48% (n=49/102) have been respirator fit-tested. Of the healthcare workers who needed to use respirator for work but were yet to be fit-tested, 22.6% (n=12/53) were still willing to don non-fit tested respirators for work due to the current pandemic circumstances. Conclusions: The awareness of fit testing is inadequate, and each healthcare institution should kindle a robust and active respirator fit testing program to prepare for the next pandemic.